The Shuttle puzzle [Space Suttle Columbia disaster]. - Oberg, J.
Will the Columbia catastrophe prove to have been an "accident" in the strict sense of the word? The author discusses the causes of the Challenger disaster and possible causes of the Columbia disaster. The steps that led to the Columbia disaster-paved, like the road to hell, with good intentions and judgments that each in isolation look acceptable-are still being worked out. Only then will we be able to determine whether this event deserves to be called an accident of unforeseeable and unpreventable surprises-or is the grim consequence of incompetent engineering management.
Keywords: Challenger disaster; Columbia catastrophe; Space Shuttle; Accident; Incompetent engineering management